Pop! Goes the music: a content analysis of popular music in prime-time television commercials - Farmer, Ajia (Kansas State University, 2008)
The advertising industry press has been writing about the increase in use of popular music in television commercials, yet there is little to no scholarly quantifiable data to support such press. This study investigates how popular music in television commercials is being utilized and how much is being used. A content analysis of 1,046 prime-time television commercials was conducted to further examine the use of popular music in television commercials and how its use related to observable executional variables in the manifest content. The study found that of the 574 unique commercials, 64% of the commercials used popular music. The results suggest that of the different types of music coded, popular music was in fact the most prominent. This musical prominence could be the result of the advertisers' mission to target the younger audience (18-39) and as such, use the music that is most popular among this age group. Implications for future advertising research and strategy are discussed.
Keywords: Popular music; Advertising; Content analysis; Television commercials; Mass Communications (0708)